Morphometric and morphological study of mental foramen in the malaysian population: Anatomy and forensic implications - Alias A.; Ibrahim A.; Abu Bakar S.N.; Shafie M.S.; Das S.; Nor F.M. (International Islamic University Malaysia, 2024)
Introduction: The mental foramen is present on either side of the body of the mandible bone. This foramen transmits mental vessels and nerves. In forensic anthropology, mental foramen may be important for differentiating sex, estimating age and identifying various races based on morphology. The main aim of the present study was to determine the position, shape and diameter of the mental foramen according to sex, age and race by postmortem computed tomography in the Malaysian population. Materials and Methods: A total of 79 dentulous patients (48 males, 31 females) from 3 age groups (18-30 years, 31- 50 years, 51-74 years) were selected for this study, and ten parameters were observed for each mandible. The parameters were divided into two morphological and eight morphometric parameters. The morphometric parameters were measured by using Osirix MD Software 3D Volume Rendering. Results: Results showed that mandibular body length and height were significantly greater in males than in females by independent t-test. (p < 0.05). However, the mandibular body height was found to decrease significantly with age in both sexes by one-way Anova. It was observed that the shape of mental foramen was 45.6% oval and 54.4% rounded. About 44.3% of them were in line with the longitudinal axis of the second premolar tooth. Conclusion: It was concluded that mental foramen may be used for identification purposes, particularly for sex, age and race determination.